Garmin among hardest hit in major wave of ransomware attacks. Issue 8 (August 2020) - Unknown
Abstract : Garmin, a major manufacturer of GPS systems, fitness trackers and other products, has been severely affected by a ransomware attack. Meanwhile, new forms of ransomware have emerged, including malware originating from North Korea.